Social Justice and K-12 Teachers’ Effective Use of OER: A Cross-Cultural Comparison by Nations - Tang, Hengtao; Bao, Yu (Journal of Interactive Media in Education, 2020)
Open educational resources (OER) have the potential to promote social justice imperatives in education, but because of the uneven provision of technical infrastructure across different countries, it remains uncertain whether the people who need OER the most are its primary beneficiaries. In K-12 education, educators play a major role in the effort to incorporate OER into classroom teaching but, even if they are able to source such resources (overcoming the “first-level digital divide”), many lack the practical capacity to effectively use (e.g., adapt) OER (the “second-level digital divide”). This exploratory research paper employs a cross-cultural perspective to interrogate how the second-level digital divide shapes K-12 teachers’ effective use of OER. With the goal of understanding how this divide influences OERs’ potential to enhance social justice, this research attempts to identify the factors accounting for teachers’ effective use of OER – and any reception gap – between different countries by conducting a series of stepwise logistic regressions applied to a largescale survey of K-12 educators. It does so by assessing OER use amongst 675 K-12 educators around the world in relation to their developmental and cultural contexts, as expressed through the Human Development Index, the Gender Development Index, and Hofstede’s six dimensions of national culture. The findings of this exploratory study provide new insights to support OER adoption in K-12 settings worldwide from a cultural perspective.
Keywords: K-12 teachers; cultural dimensions; exploratory research; open educational resources; second-level digital divide; social justice; stepwise logistic regression